Principal accountability at private secondary schools - Sherrilyn M. Billger (Institute for the Study of Labor (IZA), 2007)
Increasing interest in voucher programs and privatizing public schools reveals a commonly-held belief that private schools are better able to produce a quality education. While state and national standards do not directly affect these schools, their private control yields strong student performance. To contribute to the general discovery about private schools, I use SASS and Census data to investigate accountability and outcomes at private secondary schools, focusing on principals, student outcomes, and administrator effectiveness. I find that principals are not rewarded for facing accountability or for exercising autonomy. OLS and quantile regression results also suggest no direct benefit for strong students at high quality schools. However, accountability does improve student outcomes at the (conditionally) weakest schools.
Keywords: J3; 370; Principal pay; accountability; private schools; Privatschule; Führungskräfte; Besoldung; Wirtschaftliche Effizienz; Bildungsniveau; USA